Building nurse education capacity in India: insights from a faculty development programme in Andhra Pradesh - Evans, Catrin; Razia, Rafath; Cook, Elaine (BioMed Central, 2013)
Background: India faces an acute shortage of nurses. Strategies to tackle the human resource crisis depend upon scaling up nursing education provision in a context where the social status and working conditions of nurses are highly variable. Several national and regional situation assessments have revealed significant concerns about educational governance, institutional and educator capacity, quality and standards. Improving educational capacity through nursing faculty development has been proposed as one of several strategies to address a complex health human resource situation. This paper describes and critically reflects upon the experience of one such faculty development programme in the state of Andhra Pradesh.